1982
DOI: 10.1093/ajcn/36.6.1093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing on digestibility and the blood glucose response: a study of lentils

Abstract: To test the effect of processing on digestibility and the glycemic response to a leguminous seed, a group of eight healthy volunteers took a series of breakfast test meals containing either lentils which had been processed in four different ways or the same amount of carbohydrate as white bread. Lentils, boiled for 20 min, resulted in a flattened blood glucose response by comparison with bread. This was unaltered by blending the lentils to a paste or boiling them for an additional 40 minutes. However the blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
113
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(123 citation statements)
references
References 24 publications
8
113
1
1
Order By: Relevance
“…Similarly, banana bread and pasta formulated with yellow pea flour demonstrated low-glycemic response properties compared with pulse-free controls made with whole wheat flours (24). In the early 1980s, Jenkins et al (21) showed that grinding and drying cooked lentils influenced blood glucose response. Precooking red kidney bean flour also resulted in higher glycemia compared with boiled whole beans (37).…”
mentioning
confidence: 99%
“…Similarly, banana bread and pasta formulated with yellow pea flour demonstrated low-glycemic response properties compared with pulse-free controls made with whole wheat flours (24). In the early 1980s, Jenkins et al (21) showed that grinding and drying cooked lentils influenced blood glucose response. Precooking red kidney bean flour also resulted in higher glycemia compared with boiled whole beans (37).…”
mentioning
confidence: 99%
“…The consumption of these types of food has been encouraged in the USA by the American Cancer Society (ACS), the American Heart Association (AHA) and the American Diabetes Association (ADA) as part of a healthy diet. Lentils as a good source of dietary fiber and enzyme inhibitors such as phytates, tannins, antigenic proteins have been studied in the treatment of diabetes (Jenkins et al, 1982). According to Jenkins et al (1982), the incorporation of lentils in a diet can help to manage postprandial glycemia in normal and diabetic patients due to enzyme inhibitors ability to decrease the rate of carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Lentils as a good source of dietary fiber and enzyme inhibitors such as phytates, tannins, antigenic proteins have been studied in the treatment of diabetes (Jenkins et al, 1982). According to Jenkins et al (1982), the incorporation of lentils in a diet can help to manage postprandial glycemia in normal and diabetic patients due to enzyme inhibitors ability to decrease the rate of carbohydrate metabolism. Also, peas as source of an array of nutrients and phytochemical have been shown to provide some health benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported by several researchers that heat treatment significantly improves the protein quality in pulses by destruction or inactivation of the heat labile anti-nutritional factors (Jenkins et al 1982;Deosthale 1982;Khokhar and Chauhan 1986;Wang et al 1997;Vijayakumari et al 1998). Therefore, it may be useful to apply treatments for loosening the hulls by thermal means.…”
Section: Introductionmentioning
confidence: 99%